Kinetic models on quality changes during heat blanching of some fruit and vegetables - Abdul Halim, Arinah Adila; Ariffin, Siti Hajar; Zainol@Abdullah, Wan Nor Zanariah; Azmi, Nazatul Shima (HH Publisher, 2022)
Blanching have been used as a thermal treatment in food processing especially as a pre-treatment of processes such as drying, freezing and canning that includes fruits and vegetables. Blanching treatment helps to remove the microorganisms, lengthen the shelf life and enhancing the color, flavor and texture of the fruits and vegetables. However, blanching affected the nutrients and characteristics of fruits and vegetables that contributes to the quality changes of the fruits and vegetables fruit. Thus, it is necessary to study about the quality changes during heat blanching of fruits and vegetables fruit to study the changes of the characteristics, nutrients and properties of the fruits and vegetables fruit. Kinetic modelling on the quality changes of fruits and vegetables fruit is crucial for quality modelling and quality control of fruits and vegetables fruit during the heat blanching treatment. Kinetic modelling is also important to identify which temperature and time that is optimum for the quality of fruits and vegetables after the heat blanching treatment, also to identify the kinetic trend of the properties of fruits and vegetables fruit that were affected. In this paper, general aspects of blanching process are discussed. Properties and methods to measure the quality changes were discussed. Models of kinetic according to the properties and characteristics affected by the blanching treatment were also reviewed. Keywords: fruits and vegetables; blanching; kinetic modelling; quality changes; thermal treatment